Reflections of experts by experience and research team members on research and development about a sensitive issue that attracts stigma. (16th February 2023) - Howlett, Helen; Catterick, Maria; Charlotte; Karen; Cheyenne; Onukwugha, Franklin; Roberts, Helen; Dyson, Judith; Smith, Lesley
Abstract : page_1 other To reduce the number of alcohol-exposed pregnancies in antenatal care in the UK, the CHAMPION study objective was to design appropriate training and resources to develop the midwifery skills and confidence required to have an effective conversation about alcohol with pregnant women. Women with lived experience of drinking during pregnancy and 'birth mums' of a child with fetal alcohol spectrum disorders (FASD) were central to the co-creation process of the CHAMPION study. Some remarkable unintended positive outcomes resulted from this collaboration process for the women involved. They include increased confidence levels from newfound friendships with other mothers of children with FASD, and an acceptance that societal influences had a significant role to play in their page_2 other personal situations. Reflecting on this authentic co-creation process has elicited important learning outcomes to inform future research design. The significance of excellent communication channels, robust support networks and genuinely valuing and respecting experts by experience as equal partners should not be underestimated.